1989
DOI: 10.1093/nar/17.24.10259
|View full text |Cite
|
Sign up to set email alerts
|

High resolution footprinting ofEcoRI and distamycin with Rh(phi)2(bpy)3+, a new photofootprinting reagent

Abstract: The complex bis(phenanthrenequinone diimine)(bipyridyl)rhodium(III), Rh(phi)2(bpy)3+, cleaves DNA efficiently in a sequence-neutral fashion upon photoactivation so as to provide a novel, high resolution, chemical photofootpring reagent. Photofootprinting of two crystallographically characterized DNA-binding agents, distamycin, a small natural product which binds to DNA in the minor groove, and the endonuclease EcoRI, which binds in the major groove, gave respectively a 5-7 base pair footprint for the drug at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…The results of these studies indicated that this distance is 17 bp (see supplemental material). Moreover, prior studies have determined the distance between the leading edge of vRNAP and the active site to be 15 bp (39), and the distance between the upstream edge of EcoRI* and the first G in GAATTC to be 2 bp (39). The sum of these two distances agrees well with our estimate of 17 bp.…”
Section: Dna/rna Hybrid Strength Affects Nph I-mediated Transcript Resupporting
confidence: 87%
“…The results of these studies indicated that this distance is 17 bp (see supplemental material). Moreover, prior studies have determined the distance between the leading edge of vRNAP and the active site to be 15 bp (39), and the distance between the upstream edge of EcoRI* and the first G in GAATTC to be 2 bp (39). The sum of these two distances agrees well with our estimate of 17 bp.…”
Section: Dna/rna Hybrid Strength Affects Nph I-mediated Transcript Resupporting
confidence: 87%
“…An advantage of the diplatinum complex is that it does not produce a diffusible intermediate such as ؒOH, which is easily quenched by reagents commonly used to maintain the native form of the protein, such as DTT or glycerol. The complex Rh(phi) 2 (bpy) 3+ also exhibits a sequence-neutral photocleavage pattern and has been used to footprint the binding of both EcoRI and distamycin on a restriction fragment (44).…”
Section: Hydrogen Abstractionmentioning
confidence: 99%
“…28; J. G. Collins, T. P. Shields, and J.K.B., unpublished data). Phi complexes of rhodium cleave DNA and RNA upon photoactivation and thus are also useful as probes of higher-order structures in nucleic acids and as high-resolution DNA photofootprinting reagents (29)(30)(31)(32)(33)(34)(35). The absorption spectrum ofRu(phen)2dppz2+ is characterized by a metal-to-ligand charge transfer transition centered on the dppz ligand, and the emission from this state in nonaqueous solution can be quenched by electron acceptors (36).…”
mentioning
confidence: 99%